Molecular Dynamics Simulation for Thiolated Poly(ethylene glycol) at Low‐Temperature Based on the Density Functional Tight‐Binding Method. Issue 12 (17th October 2022) - Li, Shi; Chen, Lei; Gui, Xuefeng; He, Daguang; Hu, Jiwen; Huang, Zhenzhu; Lin, Shudong; Tu, Yuanyuan; Dong, Yonglu
Abstract: The condensed structure of a material is the basis for the properties of polymeric materials, where the crystalline structure is the most ordered conformation of the polymer condensed structure. The mechanical properties are one of the most fundamental properties of polymer materials and the crystalline state has an important influence on the mechanical properties. Here, the optimal chain conformation and the effect of optimization time on the temperature and energy of molecular thermodynamics and molecular dynamics are investigated using thiolated poly(ethylene glycol) as the base material. The simulation results show that the number of optimization steps and the simulation time are closely related to the molecular conformation of polymer single crystals. A new perspective is provided for exploring intra‐ and intermolecular interactions in polymer crystals and revealing their nature, establishing the link between chain structure and mechanical properties of materials, and designing and manufacturing polymer crystalline materials with better mechanical properties. Abstract : A new perspective is provided here for exploring intra‐ and intermolecular interactions in polymer crystals and revealing their nature, establishing the link between chain structure and mechanical properties of materials, as well as designing and manufacturing polymer crystalline materials with better mechanical properties.